Welcome to the New Issue of GIPAN: Interdisciplinary Approach to Research and Innovation - Gautam, Bhim Lal; Fritz, Emilia; Khatiwada, Karnakhar; Poudel, Prem Prasad (Gipan, 2024)
This editorial review of Gipan Volume 6 (1) introduces the smooth shift from previous disciplinary focus on Gipan to more multidisciplinary one, in which papers belonging to issues in linguistics and applied linguistics (including language teaching) have been incorporated. The primary purpose of bringing in the interdisciplinary focus is to bring the cross-cutting issues across disciplines into broader discourse. This review starts with a brief background information relating to the journal, highlights the themes as they emerge in the issue, summarizes the papers included and concludes with a call for action in support of the new multidisciplinary initiative. Acknowledging the contribution from the individuals and institutions involved in bringing the journal in this form, the review ends with a call on the established scholars and practitioner researchers to cross over disciplinary boundaries and create an international platform for intellectual exchange which will ultimately lead towards a positive social transformation.